Science and technology for development : report on the United Nation conference on the application of science and technology for the benefit of the less developed areas (United Kingdom : United Nations, 1963)
This report gave a narrative account of the United Nation Conference on the application of science and technology for the benefit of the less developed areas.
Vol. IIII: Agriculture
Includes bibliographical references and index.
osa 11/06/18
Loans
Keywords: Economic planning; Development